Dynamic Output Feedback Consensualization of Uncertain Swarm Systems with Time Delays. Issue 4 (6th December 2012) - Xi, Jianxiang; Shi, Zongying; Liu, Guangbin; Zhong, Yisheng
Abstract Consensus analysis and design problems of high‐dimensional discrete‐time swarm systems in directed networks with time delays and uncertainties are dealt with by using output information. Two subspaces are introduced, namely a consensus subspace and a complement consensus subspace. By projecting the state of a swarm system onto the two subspaces, a necessary and sufficient condition for consensus is presented, and based on different influences of time delays and uncertainties, an explicit expression of the consensus function is given which is very important in applications of swarm systems. A method to determine gain matrices of consensus protocols is proposed. Numerical simulations are presented to demonstrate theoretical results.